Influences and interactions of inundation, peat, and snow on active layer thickness - Adam L. Atchley; Ethan T. Coon; Scott L. Painter; Dylan R. Harp; Cathy J. Wilson (Geophysical Research Letters)
Abstract Active layer thickness (ALT), the uppermost layer of soil that thaws on an annual basis, is a direct control on the amount of organic carbon potentially available for decomposition and release to the atmosphere as carbon‐rich Arctic permafrost soils thaw in a warming climate. We investigate how key site characteristics affect ALT using an integrated surface/subsurface permafrost thermal hydrology model. ALT is most sensitive to organic layer thickness followed by snow depth but is relatively insensitive to the amount of water on the landscape with other conditions held fixed. The weak ALT sensitivity to subsurface saturation suggests that changes in Arctic landscape hydrology may only have a minor effect on future ALT. However, surface inundation amplifies the sensitivities to the other parameters and under large snowpacks can trigger the formation of near‐surface taliks.